The role of ABCA12 in neurodegenerative diseases – a review of molecular mechanisms and potential therapeutic implications - Kumar, Daksh; Goel, Falguni; Rai, Sachchida Nand (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. ABCA12 a member of the ATP-binding cassette transporter superfamily, is known to be involved in lipid transport and in the formation of the skin barrier. However, recent evidence also suggests its implication in the pathophysiology of neurodegenerative diseases. This review focuses on the molecular mechanisms that could link ABCA12 to neurodegenerative processes and its potential as a therapeutic target. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A literature review search was conducted between 200 and 2024 via the databases, which included PubMed, Scopus, and Web of Science. There, pertinent studies with relevance to ABCA12 involvement in neurodegenerative diseases were searched. This study reviewed pertinent articles on the expression patterns of ABCA12 and its molecular inter actions, as well as its contribution to cellular processes, such as lipid homeostasis, inflammation, and neuronal integrity. The analysis further included studies on ABCA12 mutations and their associations with neurodegenerative pathologies such as Alzheimer’s disease, Parkinson’s disease, and Huntington’s disease. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Analysis of literature. The results from the analysis showed that ABCA12 dysfunction led to disturbances in lipid metabolism, accompanied by increased oxidative stress, neuroinflammation, and compromised integrity of the neuronal membrane. The results imply that mutations or dysregulation of ABCA12 exaggerates amyloid-beta aggregation in Alzheimer’s disease and dopaminergic neuron loss in Parkinson’s disease. Finally, pathways of ABCA12 functionally interact with other core neurodegenerative mechanisms, which include autophagy dysregulation and mitochondrial dysfunction. Preliminary preclinical data indicate that altering ABCA12 expression or function diminishes neuroinflammation and restores cellular homeostasis. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. ABCA12 plays an important role in maintaining neuronal health and its dysfunction contributes to neurodegenerative processes. Targeting pathways related to ABCA12 seems promising to mitigate disease progression in neurodegenerative diseases. More research is still required to elucidate its precise molecular mechanisms and identify specific interventions.